Célébrer collaboration et émancipation for more than a generation - Richard, Moniques (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2025)
Célébrer le 20e volume de la revue Canadian Art Teacher / Enseigner les arts au Canada (CAT), c’est témoigner de l’essor, pour plus d’une génération, de l’éducation artistique ainsi que de la recherche et de la création en ce domaine ! C’est reconnaître l’influence et l’excellence des publications canadiennes. I would like to take advantage of this celebration to outline the transformation and continuity of some ideas that have mobilized our pan-Canadian community, and to review, in reverse, my own journey over the last two decades, from 2024 back to 2004. Je partagerai mes réflexions bilingues principalement autour des notions suivantes : génération, étiquette (labels), inclusivité, collaboration et émancipation.